Food Prices, Wages, and Welfare in Rural India - Jacoby, Hanan G. (Wiley, 2015)
With soaring food prices in recent years has come alarm about rising poverty in the developing world. Less appreciated, however, is that many of the poor in agricultural economies may benefit from higher wages. This study finds that wages for manual labor in rural India, both within and outside agriculture, rose faster in districts growing more of those crops with large producer price run-ups over the 2004–2009 period. Based on a general equilibrium framework that accounts for such wage gains, rural households across the income spectrum are found, contrary to more conventional welfare analysis, to benefit from higher agricultural prices. For non-commercial use in accordance with Wiley Terms and Conditions at http://olabout.wiley.com/WileyCDA/Section/id-820227.html